Up close and hyper-personal the formation of hyper-personal relationships in online support groups - Moya, Monik C.; Oliveros, Jurise Athena P.; Rentutar, Louie Diane V.; Reyes, Mariane Genelou S.; Sison, Maria Angelica C. (2008)
Several studies have shown that despite the lack of social cues in online interaction, people have still turned to the Internet to relate with others. This study explores the formation of relationships in the context of online support groups through the analysis of conversations and transcripts from interviews with chatters in an online community for Alzheimer's disease. Walther's theory of hyper-personal relationships was used to describe and explain the formation of different kinds of relationships online. To explore the development of online relationships from impersonal to interpersonal and to hyper-personal, the researchers looked at the motivations, level of participation, topics discussed, and level of disclosure of the chatters in an online support group. The study concludes that through the unique features of online communities (i.e., anonymity, communication styles, and patterns of interaction), the formation of hyper-personal relationships may be formed to substitute or even surpass face-to-face relationships.